California gold rush - Roop, Peter; Roop, Connie (New York : Scholastic Reference, 2002)
Describes, in illustrations and easy text, how gold was discovered in California, how miners traveled to the gold fields, how they sought gold or found riches other ways, and their impact on California.
Gold fever! -- California or bust! -- Striking it rich! -- After the rush.
Includes bibliographical references (p. 48) and index.
790L
Accelerated Reader AR
Keywords: Frontier and pioneer life -- California -- Juvenile literature; Gold mines and mining -- California -- History -- 19th century -- Juvenile literature; California -- History -- 1846-1850 -- Juvenile literature; California -- Gold discoveries -- Juvenile literature; History; Juvenile works